Through the Looking Glass: The Role of Ethnicity and Affiliation in Responses to Terrorism in the Media - Shoshani, Anat; Slone, Michelle (Frontiers in Psychology, 2016)
This study examined whether attitudinal and emotional responses to broadcasts of images of terrorist events differ according to ethnic group (Jewish and Arab Israelis) and outgroup affiliation during an intense wave of terrorism that occurred in Israel during 2015. Participants were 118 Jewish and 110 Arab-Israelis adults randomly allocated to a terrorism or criminal violence television broadcast. State anxiety, state anger, stereotypes, and negative attitudes toward an adversary were examined prior and subsequent to the media exposure. Findings showed significant increases in anxiety, anger, stereotypes, and negative adversary perceptions in the terrorism exposure group compared to only anxiety increases in the criminal violence exposure. In the terrorism exposure group, Jewish participants showed greater increases in negative adversary perceptions of the Palestinians than Arab Israeli participants, but both groups showed similar significant increases in levels of anxiety and anger. Exposure to broadcasts of terrorism increased willingness to negotiate with the adversary among the Arab participants, but not among the Jewish participants. In the terrorism exposure group, both Jewish and Arab Israelis with high affiliation with the Palestinian cause showed less increases in stereotypes than those with low affiliation. Findings emphasize the role of ethnicity and outgroup affiliation in responses to media exposure to terrorism images.